STUDY OF WILDLIFE SPECIES WEALTH USING CAMERA TRAP IN SIPURAK HOOK AREA KERINCI SEBLAT NATIONAL PARK AREA - Farhan Reza Pahlevi; Agus Susatya; Hery Suhartoyo (Journal of Science Innovare, 2022)
Indonesia is known as one of the countries with the highest biodiversity in the world, this research was carried out from November 2020 to January 2021 in the Sipurak area, Merangin district, Jambi province. Camera traps are installed on tree trunks with an average height of 30 - 45 cm above the ground, the camera position is facing the path at a distance of 2.5 meters from the edge of the path and calculates the direction of light coming. The results of this study found 20 species of wild animals from 13 families, with a total of 201 independent event (IE) photos with the highest relative abundance of animals, namely, (Tupai javanica) of 12.95% and the lowest animal of Sumatran tiger (Panthera tigris sumatrae) by 0.72%.